1983
DOI: 10.1288/00005537-198309000-00014
|View full text |Cite
|
Sign up to set email alerts
|

The argon laser in surgery for chronic ear disease and otosclerosis

Abstract: The use of the argon laser in chronic ear disease and otosclerosis surgery is reviewed. Its advantages and limitations are discussed, and safe parameters for use established. The argon laser is an effective tool to remove, cut, and coagulate tissue. It was used in over 500 microsurgical otologic procedures without deleterious effects. One hundred primary laser stapedotomies were performed, and the audiological results were compared to those obtained using conventional small fenestra stapedectomy techniques. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0
5

Year Published

1985
1985
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(52 citation statements)
references
References 5 publications
2
45
0
5
Order By: Relevance
“…In average, the operation time reduced about onethird and the completion rate of stapes surgery increased about one-fifth after implementing diode laser in our department. Several studies have also demonstrated that regardless of devices used to create the stapedotomy (manual perforator, micro-drill or lasers) no significant difference in either post-operative ABG closure or postoperative sensorineural hearing loss can be found [4][5][6][7][8][9][10]. Some studies have shown that micro-drill is superior to manual perforator [14] and CO2-laser is superior to potassium-titanyl-phosphate (KTP) laser [15], but these improvements were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In average, the operation time reduced about onethird and the completion rate of stapes surgery increased about one-fifth after implementing diode laser in our department. Several studies have also demonstrated that regardless of devices used to create the stapedotomy (manual perforator, micro-drill or lasers) no significant difference in either post-operative ABG closure or postoperative sensorineural hearing loss can be found [4][5][6][7][8][9][10]. Some studies have shown that micro-drill is superior to manual perforator [14] and CO2-laser is superior to potassium-titanyl-phosphate (KTP) laser [15], but these improvements were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most remarkable technical innovations was the introduction of lasers in stapes surgery already three decades ago [2,3]. However, several earlier and latter studies have shown no significant differences between laser-assisted, micro-drill and manual microsurgical stapedoplasty with regard to hearing outcome [4][5][6][7][8][9][10]. Instead of better hearing outcome, the micro-drill and/or laser appears to be very helpful to provide greater accuracy during precise manipulations and thereby reduce surgical trauma, which is important advantages regarding patients' safety compared to handheld instruments [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…He reported on cutting through middle ear adhesions and reshaping autogenous bony columellas during reconstruction of the ossicular chain [19]. Having used the argon laser in more than 500 tympanoplasties, McGee [20] also reported on his favourable experiences. The KTP laser which was developed in 1986 has become one of the most popular lasers in middle ear surgery [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Die Laserstapedotomie weist gegenüber der konventionellen Stapedotomie einige Vorteile auf. So konnten klinische Studien zeigen, dass die Laserstapedotomie im Vergleich zu konventionellen Eingriffen weniger Innenohrschädi-gungen und vestibuläre Störungen verursacht [6,15,29,34,45,53].…”
Section: Historische Entwicklungunclassified